2018
DOI: 10.1093/nar/gky1198
|View full text |Cite
|
Sign up to set email alerts
|

DevelopmentalXistinduction is mediated by enhanced splicing

Abstract: X-inactive-specific transcript (Xist) is a long noncoding RNA (lncRNA) essential for inactivating one of the two X chromosomes in mammalian females. Random X chromosome inactivation is mediated by Xist RNA expressed from the inactive X chromosome. We found that Xist RNA is unspliced in naïve embryonic stem (ES) cells. Upon differentiation, Xist splicing becomes efficient across all exons independent of transcription, suggesting interdependent or coordinated removal of Xist introns. In female cells with mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…XIST is selectively expressed from and physically coats the future inactive X chromosome in XX female cells ( 38 ). Experiments in murine embryonic stem cells showed that developmental Xist induction is mediated by enhanced splicing ( 39 ). XIST displayed significant DAS in 23 tissues, comprising two SE, one A3SS, and one MXE event (fig.…”
Section: Resultsmentioning
confidence: 99%
“…XIST is selectively expressed from and physically coats the future inactive X chromosome in XX female cells ( 38 ). Experiments in murine embryonic stem cells showed that developmental Xist induction is mediated by enhanced splicing ( 39 ). XIST displayed significant DAS in 23 tissues, comprising two SE, one A3SS, and one MXE event (fig.…”
Section: Resultsmentioning
confidence: 99%
“…An important question now is how the proteins that interact with repeat E relate to one another. Neither endogenous polypyrimidine tract-binding protein 1 (PTBP1) nor FLAG-matrin 3 (MATR3), both of which interact in vivo (Smola et al, 2016; Stork et al, 2019) (Pandya-Jones et al, 2020), were seen enriched around H3K27me3-marked Xis in fibroblasts (Supplemental Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…Although the expression of the XBP1 gene differed among various conditions, the expression levels of uXBP1 and sXBP1 may be measured more reliably than those of other housekeeping genes by using tXBP1, which has been designed as a component common to both uXBP1 and sXBP1. In 2018, Stork and colleagues also reported the use of designed qPCR primer pairs to measure total, spliced, and unspliced Xist transcripts, and normalized the spliced and unspliced Xist to total Xist [31]. In addition, several studies have shown that quantification using the total gene transcript is more accurate for quantifying housekeeping genes [32, 33].…”
Section: Discussionmentioning
confidence: 99%